Bleomycin Aggravates Atopic Dermatitis via Lung Inflammation in 2,4-Dinitrochlorobenzene-Induced NC/Nga Mice - Sung, Yoon-Young; Kim, Seung-Hyung; Yang, Won-Kyung; Park, Yang-Chun; Kim, Ho Kyoung (Frontiers in Pharmacology, 2018)
Atopic dermatitis (AD) is a chronic inflammatory skin disease. Bleomycin (BLM) contributes to the induction of pulmonary inflammation and fibrosis in animals. Although skin and lung tissue inflammation is closely related in the pathogenesis of allergic diseases, a proper animal model for investigating the relationship between skin and lung inflammation is lacking. Therefore, we developed a mouse model of AD with relapsing dermatitis and pulmonary fibrosis caused by the administration of allergen and BLM. The present study determined whether lung injury caused by the bronchial application of BLM would exacerbate AD-like allergic inflammation induced by 2, 4-dinitrochlorobenzene (DNCB) in NC/Nga mice. NC/Nga mice treated with BLM and DNCB had increased severity of clinical symptoms and airway hyperresponsiveness as well as increased inflammatory cell infiltration and collagen deposition in the dorsal skin and lung. Compared to normal mice, interleukin (IL)-6 and tumor necrosis factor (TNF)-a production in bronchoalveolar lavage fluid were increased in NC/Nga mice treated with both DNCB and BLM and in animals treated with DNCB alone. Administration of BLM and DNCB increased the levels of IL-4 and IL-13 production in spleen cells and eotaxin 2 mRNA expression in dorsal skin, compared to NC/Nga mice treated with DNCB alone. The total cell numbers in axillary lymph node, bronchoalveolar lavage, and thymus were increased in DNCB-BLM mice compared to those in mice treated with DNCB alone. Administration of BLM and DNCB increased the numbers of cluster of differentiation 4 (CD4)+ T cells and CD11b+granulocyte-differentiation antigen-1 (Gr-1)+ cells among peripheral blood mononuclear cells, CD4+ cells in bronchoalveolar lavage, CD4+ and B220+CD23+ B cells in the axillary lymph node, and CD4+ cells in thymus, compared to DNCB-treated mice. The number of total, CD4+, and CD11b+Gr-1+ cells in the lung were increased in both DNCB and DNCB-BLM mice. These results demonstrate that BLM aggravates allergic skin inflammation and promotes airway hyperreactivity and lung inflammation when combined with DNCB in NC/Nga mice.